AGRÉGUESE AL CÓDIGO ORGÁNICO INTEGRAL PENAL EL MALTRATO MEDIANTE RESTRICCIÓN DE LOCOMOCIÓN A OTRA PERSONA MAYOR DE EDAD PERTENECIENTE A SU GRUPO FAMILIAR - Guerrero Veliz, Andrey Fernando (2024)
The present investigation entitled "Add to the integral penal organic code the mistreatment by means of restriction of locomotion to another elderly person belonging to their family group", has the purpose of determining a penalization to the individuals who mistreat under the standard of locomotion to the elderly, in addition it is carried out because of the main articles 34,35,36 of the Constitution of the Republic of Ecuador and the Organic Law of the Elderly People who recognize them as groups of priority attention. On the other hand, this practice, considered a violation of human rights and international law, implies depriving the person of their ability to move and participate in society in an autonomous and safe manner. These actions may include forced confinement, isolation or denial of access to basic services and social relations. International law seeks to prevent and punish this type of abuse, protecting the fundamental rights of the person concerned and promoting equality and dignity within the family and society at large. Likewise, in Colombia's international criminal law, domestic abuse or violence is mainly regulated by Law 1257 of 2008, which establishes measures to raise awareness, prevent and punish forms of violence and discrimination against women, as well as Law 294 of 1996, which defines the crime of domestic violence. These laws contemplate the restriction of locomotion and other types of mistreatment within the family environment, in addition, the Puerto Rican penal norm, Law No. 54 of 1989, includes provisions for the protection against mistreatment and restriction of locomotion of elderly persons within their family group, which typifies diverse crimes and illicit conducts, and includes situations of mistreatment and restriction of locomotion. Thus, the present work has the objective of carrying out a doctrinal, legal and comparative study of how this anti- juridical activity should be penalised in Ecuador, taken from the Colombian criminal legislation, which violates the main rights of older adults under the framework of protection of their relatives within the home, without reason of being involved in actions that incur physical and psychological mistreatment of their state as a person with rights.